PROBLEMATICS IN LEARNING THROUGH THE QUALITY OF TEACHER TEACHING MATERIALS IN NAPAI STATE PRIMARY SCHOOL, WEST ACEH - Mahrini; Siti Mayang Sari; Mhd. Syafii; Fitriani Manurung; Sariakin (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This research was conducted regarding the phenomenon of low teacher competence. The focus of this research is on teachers' internal and external problems in the teaching and learning process (PBM). The aim of this research is to find out: 1) the problems of the teaching profession; 2) efforts to improve the quality of education at Napai State Elementary School, West Aceh Regency. This research uses a qualitative descriptive research approach. Data collection techniques use models: observation, interviews, and documentation. The results of the research show that: 1) teacher problems consist of internal problems, including: (a) pedagogical competence, namely weak control of the class, poor innovation and creativity, low interest in reading, lack of mastery of good assessment techniques and teachers lacking or even not mastering learning media which is based on information technology, (b) professional competence, namely lack of mastery of the material, (c) personality competence, namely lack of love for the profession. Meanwhile, external problems include: class size, learning atmosphere, limited learning facilities and resources, discipline and available libraries. 2) the solution/effort made to overcome this problem is by empowering human resources and existing facilities to support improving the quality of education,